ANALISIS LAPORAN KEUANGAN PERUSAHAAN BUMN SEKTOR TRANSPORTASI DAN PERGUDANGAN UNTUK MENILAI KINERJA KEUANGAN SEBELUM DAN MASA PANDEMI COVID-19 (STUDI KASUS PADA PT KERETA API INDONESIA (PERSERO) TAHUN 2018-2020) - Septina Rahma Darmayati; Suyatmin Waskito Adi (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
The purpose of this study was to determine the financial performance of state-owned companies at PT Kereta Api Indonesia (Persero) before and during the 2018-2020 covid-19 pandemic based on the results of financial statement analysis which is expected to be able to provide information on financial performance results before and during the covid-19 pandemic to the public. company as a material for decision making and the general public. This study uses a quantitative descriptive research method in the form of secondary data derived from the financial statements of PT Kereta Api Indonesia (Persero) which consists of an income statement, a statement of changes in equity and a balance sheet obtained from https://ppid.kai.id/. This study uses data analysis techniques in the form of financial ratios consisting of liquidity ratios, solvency ratios, activity ratios and profitability ratios. Based on the results of this study, it shows that financial performance can not be said to be good considering the impact of the covid-19 pandemic in 2020 which caused a decrease in revenue and the PPKM/PSBB policies issued by the government resulted in a significant decrease in passenger volume.